Indian administrative law - Kagzi, Mangal Chandra Jain (New Delhi, 2002)
This revised 6 Edition of Kagzi's "The Indian Administrative Law" is sure to be a fresh and nice addition to the shelves of Lawyers, Law Professors, Judges, Administrators, Tribunal Members and Researchers. It should be an unavoidable accretion to law libraries in India as also in many other countries. Over the years the developments in administrative law in India have really been fast and also pragmatic. The activised judicial control of administrative action and discretion, liability of administration and modes of redressal of citizens' grievances and allegations of administrative corruption have really been constructive and effective. Written in a clear and lucid manner, the book contains a good deal of matter, a lot of information about the relevant legislation, ombudsman inquiries, public interest litigation, remedy and administrative tribunal procedure. The book is both comprehensive and handy. Unlike other books this work is in true original Kagzi's style.
Keywords: Administrative law-India